Primary ossifying fibroma of the proximal phalanx in a horse. (4th February 2019) - Balducci, J.; Selberg, K.; Pool, R.; Radue, R. P.
Summary: A primary ossifying fibroma was found at necropsy in a 5‐year‐old Welsh pony cross mare that was humanely subjected to euthanasia for an intractable severe left hindlimb lameness. Antemortem radiographs of the left hind pastern were characterised by articular, subchondral and cortical areas of lysis. Primary ossifying fibroma is a rare lesion of the distal limb but should be considered when there is extensive lysis extending into the medulla and proximal cortical bone.